Pendekatan Pembelajaran Berbasis Proyek untuk Meningkatkan Kemampuan Berpikir Kritis dan Kreatif Siswa Sekolah Dasar - Jannah, Rhaudahtul; Nisa, Sahrun (Lembaga Yasin AlSys, 2024)
This article reviews the literature on how project-based learning affects elementary school students' critical and creative thinking skills. Students must have critical and creative thinking skills in order to adapt and participate in an increasingly competitive global society. Unfortunately, there are still many elementary school students who do not have these abilities, this can be caused by the use of the wrong learning model. The purpose of this study is to see how the critical and creative thinking skills of elementary school children are affected by a project-based learning approach. Utilizing Google Scholar to find sources, literature review is the research methodology used. The findings of the literature study show how project-based learning can increase students' interest in taking an active role in creating, implementing and assessing projects that have real-world applications. Through this process, students should be able to think more critically and creatively as they identify problems, obtain data, create solutions and present their work to others. Therefore, project-based learning can be a useful strategy to improve primary school students' critical and creative thinking skills.